Climate Change and Livestock Production in Sierra Leone - Sesay, Abdul Rahman (Research Highlights in Agricultural Sciences Vol. 5, 2022)
Climate change is one of the world's most pressing environmental issues hurting agriculture and livestock production systems. Increasing temperatures cause heat stress in livestock, negatively affecting milk production, reproduction, and the health of animals. The purpose of this study is to assess livestock farmers' perceptions and adaptive responses to climate change in the Koinadugu District, northern Sierra Leone. A total of 126 livestock farmers were chosen from four chiefdoms. A semi-structured questionnaire was used to gather the information. The meteorological time series data was used to assess the temperature and precipitation records of the district. The Statistical Package for Social Sciences (SPSS) version 23.0 and excel were used to analyze the data. The result of the study shows that the farmers are aware of climate change by essential indications such as an increase in humidity (82.5%), increasing heat waves (77.0%), and decreased rainfall (54.0%). The shortages of animal feed (\(\bar{x}\) = 4.14), water scarcity (\(\bar{x}\) = 4.10), higher veterinary care expenditures (\(\bar{x}\) = 4.25), and increase in the spread of diseases (\(\bar{x}\)= 3.14) are some of the impacts of climate change on livestock production. The adaptation strategies employed by the farmers include a reduction of livestock population (87.3%), vaccination of animals (95.2%), migration along with animals during adverse climatic conditions (75.4%), and provision of salt and urea molasses block (70.6%). The factors impeding the farmer's climate change adaptation include inadequate access to veterinary services, inadequate forage and pasture, scarcity of water resources, a lack of capital, inadequate information about climate change, and inadequate infrastructure. Therefore, the government should pursue strong policies to help livestock farmers adjust to climate change in the long run.